2021
DOI: 10.1029/2020wr027744
|View full text |Cite
|
Sign up to set email alerts
|

Floodplains in the Anthropocene: A Global Analysis of the Interplay Between Human Population, Built Environment, and Flood Severity

Abstract: This study presents a global explanatory analysis of the interplay between the severity of flood losses and human presence in floodplain areas. In particular, we relate economic losses and fatalities caused by floods during 1990–2000, with changes in human population and built‐up areas in floodplains during 2000–2015 by exploiting global archives. We found that population and built‐up areas in floodplains increased in the period 2000–2015 for the majority of the analyzed countries, albeit frequent flood losses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 108 publications
3
32
0
Order By: Relevance
“…Despite the variability in the datasets, we consistently found that the population size has increased in urban areas on the floodplain. It is difficult to attribute the accelerated urbanization rates on the floodplain as driven by population or related to commercial and industrial purposes 16 , but these results do agree with recent work that wound that built-up areas and population on the floodplain have increased in most of the world's countries 13 .…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Despite the variability in the datasets, we consistently found that the population size has increased in urban areas on the floodplain. It is difficult to attribute the accelerated urbanization rates on the floodplain as driven by population or related to commercial and industrial purposes 16 , but these results do agree with recent work that wound that built-up areas and population on the floodplain have increased in most of the world's countries 13 .…”
supporting
confidence: 81%
“…Recent work shows that built-up areas on floodplains have increased 9 , although most studies have been regional 10,11 without a global assessment 1 of floodplain encroachment in both space and time. Moreover, other recent studies have examined the relationship between population dynamics and flooding but have focused on the population response to flood events [12][13][14] . In this paper, we combined maps of fluvial and pluvial flood inundation with maps of urban area changes to quantify floodplain encroachment globally as a function of flood probability rather than the actual occurrence of flooding.…”
mentioning
confidence: 99%
“…However, major urban settlements around the world are still located in floodplain areas or deltas [2]; on average, every year, more than 100 million people are affected by flooding [3,4]. Furthermore, economic flood losses and flood fatalities are on the rise, due, among other factors, to the value of assets in floodplains and the enhanced frequency and magnitude of floods [1,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Di argue that flood hazard maps and hydrogeomorphic floodplain maps are complementary and should both be used for identifying flood-prone zones in data-scarce regions, following the precautionary principle (Foster et al, 2000). The recently developed global floodplain map GFPLAIN250m (Nardi et al, 2019), hereafter GFPLAIN, built by hydrogeomorphic terrain analysis, has raised interest due to its potential for large-scale riverine flood risk applications (Akhter et al, 2021;Mazzoleni et al, 2020;Nardi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%